A Qualitative Analysis of Teachers’ Perception of Classroom Pedagogical Accompaniment Program - Arrellano, Rodrigo; García, Leidy Y.; Philominraj, Andrew; Ranjan, Ranjeeva (Frontiers in Education, 2022)
The need to increase educational quality has led public policymakers to create and implement strategies for improving teachers’ skills. One such strategy, adapted in Chile, is the classroom accompaniment program, which has become a case of teacher professional development. The present study seeks to understand the meaning attributed by public schoolteachers to the classroom accompaniment program. This qualitative research is a case study framed within an interpretive paradigm, in which semi-structured interviews were conducted to collect data. A content analysis was done with 4 categories and 10 subcategories of meanings attributed to the program by teachers. The results show opposed perceptions about the existing accompaniment program. On one hand, some teachers rate it positively and consider it beneficial for them and their students, who also received adequate feedback. On the other hand, another group of teachers considered that there were no positive contributions to their work performance, with impacts including greater reticence during the in-class observation process. Thus, the study concludes that the initial orientations and instruction regarding the role of the observing teacher are fundamental for the classroom accompaniment process to be effective and that it can be a valuable tool to apply for improving teacher performance.